Television as a symbolic culture - Andung, Petrus Ana (Teorija in praksa, 2018)
Television is part of the daily life of the border society of Indonesia and Timor Leste. Like a ritual, they interact with television every day. This article aims to analyse the meaning construction of television given by the border communities of the villages of Napan and Bobometo. This study used ethnography media, primarily micro ethnography. The results show the position held by television is equivalent to other valuable materials. These border communities interpret both technology and television text according to their socio-cultural context. The audiences in Indonesia generally regard television as a symbol of convenience and way to escape from problems at home. Meanwhile, for those in Bobometo in Timor Leste television is more a tool for strengthening social relations and a symbol of economic success.
Keywords: Borderlands; Ethnography; Etnografija; Meaning; Obmejna območja; Pomen; Television; Televizija